China’s Mediation of the Saudi-Iranian Rapprochement and its Implications on Regional Peace and Security - Sevilla, Henelito Jr A. (UI Scholars Hub, 2024)
The Middle East’s geopolitical landscape during the Cold War was characterized by ideological and religious differences among regional powers and their conflicting allegiances to the United States and the Soviet Union. Iran and Saudi Arabia held vast energy reserves and shaped regional divisions along religious and geopolitical lines. These divisions carried over to the post-Cold War era, exposing the Middle East to decades-long crises and proxy warfares. Domestic and regional problems are intensified by the interference of external powers, further deteriorating the prospects of peace and security in the region. Small countries avoid entanglement in big-power rivalries and focus on diversifying economic options beyond oil to include the non-energy sectors of trade, sci-tech, IT, and tourism, among others. The gradual disengagement of the United States in regional affairs in recent years has opened an opportunity for regional actors to rethink their policies. Domestic reforms are complemented by increasing relations with China, which establishes itself as an alternative power and credible balancer in regional affairs. To explore the changing geopolitical landscape, this paper investigates China’s mediation of the recent Saudi-Iranian rapprochement, indicating China’s initial success as a balancer in the region and the two regional powers’ prioritization of diplomacy over confrontation.